Regalos, viajes y gastos de hospitalidad. Corrupción penal en la esfera de los negocios - Carnevali Rodríguez, Raúl A. (Pontificia Universidad Católica del Perú, 2024)
There is a growing concern for having better tools to address corruption, so much so that since the 1990s various international instruments have been issued, urging States to strengthen their legislation. Although this phenomenon has traditionally been associated with the public sphere, the need to criminalize corrupt acts that take place in the private sphere is no longer questioned. Proof of this is the growing criminalization of corruption between private individuals. In this regard, one of the traditional expenses incurred by private companies is related to hospitality, such as gifts and travel aimed at promoting products or for the training of their employees and customers. However, the line that separates these expenses from improper practices that affect fair competition can be quite blurred since they could be used for bribery. Given the above, it is essential to have guiding criteria that allow one to act with clarity to prevent corrupt conduct. To this end, this paper examines the Foreign Corrupt Practices Act and the Bribery Act, since their regulations, as well as the recommendations issued by public agencies, both in the United States and the United Kingdom, provide important guiding principles that allow private companies to specify their compliance programs to have measures and procedures in place to prevent their hospitality expenses from being classified as corrupt.

Existe una creciente preocupación por disponer de herramientas claras para enfrentar la corrupción, tal es así que desde la década de los noventa del siglo pasado se han dictado diversos instrumentos internacionales, instando a los Estados a que refuercen sus legislaciones. Si bien tradicionalmente se ha asociado este fenómeno al ámbito público, hoy ya no se cuestiona la necesidad de criminalizar actos corruptos que tienen lugar en la esfera privada. Prueba de ello es la creciente tipificación del delito de corrupción entre particulares. En este orden de ideas, uno de los gastos tradicionales en los que incurren las empresas privadas dice relación con la hospitalidad, como regalos y viajes dirigidos a promocionar productos o para la formación de sus empleados y clientes. No obstante, la línea que separa estos gastos con prácticas indebidas que afectan una competencia leal puede llegar a ser bastante difusa, ya que estos se podrían emplear para sobornar. Atendido lo anterior, resulta imprescindible disponer de criterios rectores que autorizan obrar con claridad a fin de impedir conductas corruptas. Para ello, en este trabajo se examina la Foreign Corrupt Practices Act y la Bribery Act, pues de sus regulaciones, así como de las recomendaciones dispuestas por organismos públicos, tanto de Estados Unidos como del Reino Unido, emanan importantes principios orientadores que permiten a las empresas privadas precisar sus programas de cumplimiento en orden a disponer de medidas y procedimientos que eviten que sus gastos de hospitalidad sean calificados como corruptos.
Gifts, Travels and Hospitality Expenses. Criminal Corruption in the Business Field
Keywords: Hospitality; Corruption; Compliance programs; Bribery Act; Foreign Corrupt Practices Act; Bribery; Crime; Hospitalidad; Corrupción; Programas de cumplimiento; Bribery Act; Foreign Corrupt Practices Act; Soborno; Delito; https://purl.org/pe-repo/ocde/ford#5.05.01